THE USE OF ALTERNATIVE ASSESSMENT FOR UNDERGRADATE STUDENTS - Lailatul Fitriyah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Hasyim Asy'ari (Unhasy), 2021)
Abstract In recent years, there are more choices to assess students’ abilities andunderstanding in language skill. As assessment plays an important role as themeasurement in checking all steps and the results of language learning, this articledescribes a study that examine the use of alternative assessment for Indonesianundergraduate school students applied by English lectures from two differentuniversities. This study uses surveys and interviews to examine (a) the process ofalternative assessment for undergraduate students, (b) the students’ response usingalternative assessment, (c) students’ result after being assessed by alternativeassessment. So that, the conceptual frameworks taken from this study are: (a)alternative assessment’s process, (b) alternative assessment’s benefits, and (c)responsive pedagogy. This study also explores the impact of alternative assessment inassessing students in the classroom. The results of the survey revealed the majority ofteachers felt that the alternative assessment helped them in assessing the students, aswell as evaluating their beliefs and biases, thereby supporting the idea of incorporatingmore exercises and activities into English classes. The findings show that alternativeassessment is necessary to be applied in teaching and learning since by applying this kindof assessment, the students be able to understand and can practice it in their dailyactivity. Alternative assessment also has positive response from students since it isunderstandable to be practiced.